Assessmen Perkembangan Moral Agama pada AUD : Studi di TK ABA Pajangan Berbah Sleman - Bariyyah, Khoirul (Al-Athfal: Jurnal Pendidikan Anak, 2016)
This research is a kind of field research with descriptive qualitative approach. The aim of this research is (1) to describe the implementation of Moral and Spiritual Development Assessment of Early Childhood in TK ABA Pajangan, Sleman, DIY (2) to describe the techniques and instruments of assessment used in TK ABA Pajangan, Sleman, DIY (3) to describe the follow up activity in TK ABA Pajangan, Sleman, DIY. The data is collected by observation, interview and documentation study, and analized by Miles and Hubberman techniques, through data reduction, data display, and conclussion drawing. The result of the data analysis indicates that assessment of Early Childhoods’ Moral and Spiritual Development is conducted by the teacher in term of formal and informal assessments. Technique and instrument used, are always inline with the expected indicator should be reached by every student on specific theme and sub theme. The follow up activity is according to the level of each student achievement.